Microbial Desulfurization of a Crude Oil Middle-Distillate Fraction: Analysis of the Extent of Sulfur Removal and the Effect of Removal on Remaining Sulfur - Grossman, M. J. (American Society for Microbiology, 1999)
Rhodococcus sp. strain ECRD-1 was evaluated for its ability to desulfurize a 232 to 343°C middle-distillate (diesel range) fraction of Oregon basin (OB) crude oil. OB oil was provided as the sole source of sulfur in batch cultures, and the extent of desulfurization and the chemical fate of the residual sulfur in the oil after treatment were determined. Gas chromatography (GC), flame ionization detection, and GC sulfur chemiluminesce detection analysis were used to qualitatively evaluate the effect of Rhodococcus sp. strain ECRD-1 treatment on the hydrocarbon and sulfur content of the oil, respectively. Total sulfur was determined by combustion of samples and measurement of released sulfur dioxide by infrared absorption. Up to 30% of the total sulfur in the middle distillate cut was removed, and compounds across the entire boiling range of the oil were affected. Sulfur K-edge X-ray absorption-edge spectroscopy was used to examine the chemical state of the sulfur remaining in the treated OB oil. Approximately equal amounts of thiophenic and sulfidic sulfur compounds were removed by ECRD-1 treatment, and over 50% of the sulfur remaining after treatment was in an oxidized form. The presence of partially oxidized sulfur compounds indicates that these compounds were en route to desulfurization. Overall, more than two-thirds of the sulfur had been removed or oxidized by the microbial treatment.